Pasca Kondisi Implementasi Akuntansi Berbasis Akrual Pada Penyusunan Laporan Keuangan Kementerian Keuangan: Studi Etnometodologi - Syahril Djaddang; Devi Kusumawardhani (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2019)
ABSTRACT This research is qualitative research with etno-methodology approach, whereas researcher seeking the deeper meaning behind the accountancy numerals. The aim of this research is to recite the condition after accountancy accrual basis implementation in finansial record compiling at the finance ministry. Decision of Government Regulation No.71 2010 regarding Government entities to adapt and to face the challenging accountancy accrual basis implementation. Data collection was conducted with interview, filed notes, and documentation. The result of this research financial report compiling at the finance ministry. The result of this research indicated that finance ministry success to defend the unqualified opinion WTP (unqualified opinion) however, still needed stage in implementation fully to obey the government accountancy standard. There are constraint yet in accountancy technical, asset problems, in complexity understanding, human resources coordination, application problems unfully accrual basis, internal control implementation, and increment or the change of accountancy policy to decide accrual point in several the addition of theory namely Theory of Change and the Theory of Role. Theory of Change and the Theory of Role UAPA is relevant to recite the deeper meaning in this research. UAPA (accounting units of budget users) in financial ministry has an important role, as Detailer Government Accountancy Standard, Consultant Accountancy Units, Business Process Catalyst, and Locomotive Accountancy Units. ABSTRAK Penelitian ini penelitian kualitatif dengan pendekatan etnometodologi, dimana peneliti mencari kedalaman makna dibalik angka-angka akuntansi. Tujuan penelitian ini untuk mengkaji Pasca Kondisi Implementasi Akuntansi Berbasis Akrual Pada Penyusunan Laporan Keuangan di Kementerian Keuangan. Penetapan Peraturan Pemerintah Nomor 71 tahun 2010 tentang Standar Akuntansi Pemerintah membawa konsekuensi bagi Entitas Pemerintah untuk menyesuaikan tantangan implementasi akuntansi berbasis akrual. Pengumpulan data dengan melakukan interview, membuat field notes, serta dokumentasi. Hasil penelitian menunjukkan Kementerian Keuangan berhasil mempertahankan opini WTP (Wajar Tanpa Pengecualian), namun masih perlu tahapan merealisasikan sepenuhnya kepatuhan terhadap Standar Akuntansi Pemerintah. Masih ada kendala pada teknis akuntansi, permasalahan asset, pemahaman yang lebih kompleks, koordinasi sumber daya manusia, permasalahan aplikasi yang belum sepenuhnya akrualisasi, penerapan pengendalian intern, dan penambahan ataupun perubahan kebijakan akuntansi unuk menentukan titik akrualisasi beberapa peristiwa akuntansi yang memerlukan perlakuan khusus. Peneliti menemukan tambahan teori yaitu, teori Perubahan Pasca Kondisi Implementasi Basis Akrual dan Teori Peran UAPA yang relevan membantu mengkaji makna lebih dalam penelitian ini. UAPA (Unit Akuntansi Pengguna Anggaran) Kementerian Keuangan mempunyai peranan penting ibarat berperan sebagai Perinci Standar Akuntansi Pemerintah, Konsultan unit–unit Akuntansi, Katalisator Proses Bisnis, dan Lokomotif Unit-Unit Akuntansi. JEL Classificaton : H83, G02